Hsa_Circ_0007843 Acts as a mIR-518c-5p Sponge to Regulate the Migration and Invasion of Colon Cancer SW480 Cells - He, Jin Hua; Han, Ze Ping; Luo, Jin Gen; Jiang, Jian Wei; Zhou, Jia Bin; Chen, Wei Ming; Lv, Yu Bing; He, Meng Ling; Zheng, Lei; Li, Yu Guang; Zuo, Ji Dong (Frontiers in Genetics, 2020)
circRNA, a type of RNA that widely expressed in the mammalian cells, is considered to be essential in the tumorgenesis. circRNA can regulate the target gene expression by interacting with corresponding microRNA (miRNA). Our preliminary results showed that the expression levels of 1817 circRNAs were significantly different in colon cancer tissue, among in which 1236 of them were up-regulated and 581 of them were down-regulated. By using RT-PCR, we confirmed that the expressions of hsa_circ_0007843, hsa_circ_0010575, hsa_circ_0007331 and hsa_circ_0001615 were obviously higher in the colon cancer tissue than those in the normal colonic tissue, with statistical significance (P<0.05)；however, the expression levels of hsa_circ_0014879 and hsa_circRNA_401801 showed no significant difference in the normal and neoplastic colonic tissue (P>0.05). Among the circRNAs that were confirmed to be up-regulated in the colon cancer tissue, hsa_circ_0007843 was also found to be highly expressed in the colon cancer SW480 cells. Overexpression of hsa_circ_0007843 could promote SW480 cell invasion and migration, whereas down-regulation of hsa_circ_0007843 could suppress SW480 cell invasion and migration. Overexpression of hsa_circ_0007843 could promote tumor growth ,whereas down-regulation of hsa_circ_0007843 could tumor growth. The results of dual-luciferase reporter assays suggested that hsa_circ_0007843 could interact with miR-518c-5p and suppress its expression, and miR-518c-5p could interact with MMP2 and promote its expression and translation. Taken together, this study demonstrated that hsa_circ_0007843 acted as a miRNA sponge to regulate MMP2 expression via removing the inhibitory effect of miR-518c-5p on MMP2 gene translation, which further affected the SW480 cell invasion